Curatorial challenges interdisciplinary perspectives on contemporary curating - Vest Hansen, Malene; Henningsen, Anne Folke 1975-; Gregersen, Anne 1978- (Routledge research in art museums and exhibitions, 2019)
"Curatorial Challenges investigates the challenges faced by curators in contemporary society and explores which practices, ways of thinking, and types of knowledge production curating exhibitions could challenge. Bringing together international curators and researchers from the fields of art and cultural history, it provides new research and perspectives on the curatorial process and bridges the traditional gap between theoretical and academic museum studies and museum practices. It should be of great interest to academics, researchers, and postgraduate students engaged in the study of curatorial practice, museum studies, the making of exhibitions, museum communication, and art history"--